Genomic Analyses of the Quinol Oxidases and/or Quinone Reductases Involved in Bacterial Extracellular Electron Transfer - Zhong, Yuhong; Shi, Liang (Frontiers in Microbiology, 2018)
To exchange electrons with extracellular substrates, some microorganisms employ extracellular electron transfer (EET) pathways that physically connect extracellular redox reactions to intracellular metabolic activity. These pathways are made of redox and structural proteins that work cooperatively to transfer electrons between extracellular substrates and the cytoplasmic membrane. Crucial to the bacterial and archaeal EET pathways are the quinol oxidases and/or quinone reductases in the cytoplasmic membrane where they recycle the quinone/quinol pool in the cytoplasmic membrane during EET reaction. Up to date, three different families of quinol oxidases and/or quinone reductases involved in bacterial EET have been discovered. They are the CymA, CbcL/MtrH/MtoC, and ImcH families of quinol oxidases and/or quinone reductases that are all multiheme c-type cytochromes (c-Cyts). To investigate to what extent they are distributed among microorganisms, we search the bacterial as well as archaeal genomes for the homologs of these c-Cyts. Search results reveal that the homologs of these c-Cyts are only found in the Domain Bacteria. Moreover, the CymA homologs are only found in the phylum of Proteobacteria and most of them are in the Shewanella genus. In addition to Shewanella sp., CymA homologs are also found in other Fe(III)-reducing bacteria, such as of Vibrio parahaemolyticus. In contrast to CymA, CbcL/MtrH/MtoC, and ImcH homologs are much more widespread. CbcL/MtrH/MtoC homologs are found in 15 phyla, while ImcH homologs are found in 12 phyla. Furthermore, the heme-binding motifs of CbcL/MtrH/MtoC and ImcH homologs vary greatly, ranging from 3 to 23 and 6 to 10 heme-binding motifs for CbcL/MtrH/MtoC and ImcH homologs, respectively. Moreover, CymA and CbcL/MtrH/MtoC homologs are found in both Fe(III)-reducing and Fe(II)-oxidizing bacteria, suggesting that these families of c-Cyts catalyze both quinol-oxidizing and quinone-reducing reactions. ImcH homologs are only found in the Fe(III)-reducing bacteria, implying that they are only the quinol oxidases. Finally, some bacteria have the homologs of two different families of c-Cyts, which may improve the bacterial capability to exchange electrons with extracellular substrates.